O método ontopsicológico na clínica psicológica contemporânea - Azevedo, Erico de Lima (2017)
This work presents the ontopsychological method both in a theoretical and practical perspectives. In order to achieve a better understanding, in the first place, it presents its historical origins and epistemological groundings, connected mainly to Edmund Husserl and Sigmund Freud, as well as a brief report of the clinical activities developed by Antonio Meneghetti, founder of Ontopsychology, for almost four decades, his discorevies and results. For the non expert reader, a short introduction to Ontopsychology presenting four key aspects is provided: theory of knowledge, authentication psychotherapy, ontology of real and lifestyle, creating a parallel between its concepts and those of husserlian phenomenology. In the specific field of clinical psychology, a discussion on psychotherapy, psychopathology, psychosomatics and methodological proposals to clinical practice is presented. Not less important, the understanding of image as the alphabet of energy is faced, as well as the attitude for reading the semantic field and understanding its symbolic correlates in the dreams, but also the importance of the enteric nervous system (ENS) or viscerotonic brain as the elementary basis for an exact organismic perception. In the practical sphere, 162 (one hundred and sixty two) interviews conducted with the clinical attitude proposed by Ontopsychology were documented, registering not only dialogs, analysis and interventions, but also the organismic variations from ontopsychologist researcher and the 31 (thirty one) psychologist subjects, measured with oxymetry system and GDV-Kirlian technique, chosen owings to their capacity to indicate alterations in the authonomous nervous system (ANS). Results presented include process and method evaluation, practical results achieved through interventions and respective decisions, but also the analysis of physiological signals in their typical behaviour along the authentication psychotherpy sessions, revealing important aspects of dreams for a better understanding of semantic fields and, as a consequence, in the identification of the ontic intentionality from the subject in context. Linear regression analysis of results variables confirm the hypothesis that ontic intentionality directions enable excelent results in terms of utility and functionality, according to evaluations given by subjtcs themselves. Spearman, ANOVA and Scheffé tests, from another perspective, validate the semantic field discovery, as well as enhance the importance of deeper studies on the organismic criterion as the basis to a scientific comprehenstion of the ontological nexus, that is, intuition. Furthermore, three case reports are made to document the application of the ontopsychological method in authentication, psychopathology and creative leadership development, concretely illustrating the method application techniques and challenges